Effects of polyunsaturated fatty acids on mitigation of the side effects of isotretionin treatment for patients with acne vulgaris: a narrative review - Agnieszka Kaźmierska; Izabela Anna Bolesławska; Juliusz Przysławski (Family Medicine & Primary Care Review)
Acne vulgaris is one of the most common dermatological problems prompting the need for medical consultation. Currently, isotretinoin is recommended for the treatment of severe, refractory nodular acne or for prolonging remission of moderate to severe acne. Despite its high efficacy, it causes adverse effects including dryness of the mucous membranes, lips and skin, cheilitis, erythema, headache, muscle and joint pain. Long-term use of the drug can also cause liver dysfunction, lipid metabolism and also cause an increase in uric acid levels. Polyunsaturated fatty acids have been demonstrated to have beneficial effects by improving the functional status of the skin and alleviating the severity of certain skin diseases. This is especially true for gamma-linolenic acid (GLA), which in acne patients treated with isotretinoin, in addition to reducing acne lesions and papules, results in a smaller decrease in skin hydration and an increase in transepidermal water loss (TEWL). The purpose of this study was to review current literature on the effects of polyunsaturated fatty acids on the course of skin diseases, especially the alleviation of side effects of isotretinoin treatment for patients with acne vulgaris. The review shows that supplementation with polyunsaturated fatty acids seems expedient in patients with dermatoses manifesting as dry skin and after treatment with isotretinoin. GLA, in particular, should be suggested to offset the side effects of isotretinoin use.